Psychiatric hospitalization of minors in the perception of professionals at a psychiatric emergency servisse (International Seven Journal of Multidisciplinary, 2023)
The restructuring of the care model in the wake of the Psychiatric Reform evolved a mental health care policy. As a consequence, there has also been an evolution in the treatment of children and adolescents with mental disorders and a consequent increase in hospitalizations in recent years, usually due to aggressive behavior. Aim: To identify the perceptions of professionals at a psychiatric emergency service about the hospitalization of minors. Method: A descriptive, exploratory study with a qualitative approach. It was carried out in a psychiatric emergency unit of a large regional hospital in the interior of the state of São Paulo. Data was obtained through semi-structured interviews. The research subjects were ten professionals: two nurses, two doctors, three nursing assistants and three security guards. The material transcribed from the interviews was analyzed using Bardin's Thematic Content Analysis and gave rise to two thematic categories: 1) Feelings aroused by the hospitalization of minors and 2) Difficulties faced by the team. Results: The speeches revealed that the hospitalization of minors arouses varied feelings, such as impotence, a sense of responsibility and anger. The subjects also reported difficulties in coping with the internment of minors, mainly related to the inadequacy of the physical structure of the place. Final considerations: It is hoped that this study will provide food for thought on the hospitalization of minors in psychiatric emergencies, with the aim of establishing proposals for improving the situation.